PERAN PESANTREN DALAM MENUMBUHKAN MINAT WIRAUSAHA - ridwan ridwan (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2021)
One of the ways to make economic potential available is by updating new entrepreneurs, along with the development of the times and the progress of science and technology, the world of work is increasingly competing, and not a few are unemployed at the productive age, the world of formal and non-formal education has begun to improve to change the concept of education, not only learning. but it must be practiced, for provision in the future or in society The way that the pesantren does is to provide entrepreneurial training, in this study the concept of entrepreneurship training in Islamic boarding schools is broken down and what activities are carried out to foster the entrepreneurial interest of santri in pesantran, who can only recite the Qur'an, This study uses a qualitative method of choosing a location in the Al Mawaddah entrepreneurship boarding school in Kudus, Central Java, which has been around for a long time and has produced many young interpreuner. The results of this research that the almawaddah boarding school plays a very important role in fostering the interest in entrepreneurship of the students, this pesantren is not only trained in the Koran but also in entrepreneurship training and in direct practice in the place of business, so they can study religion and study entrepreneurship and get a salary, thus making the students enthusiastic about learning. and Koran and entrepreneurship,